Sensitization of Eriochromeazurol-B in Presence of Cetyldimethylethylammonium Bromide for the Microdetermination of Some Lanthanides - Anil B. Zade; Pawan P. Kalbende; Mayuri S. Umekar; Gajanan W. Belsare (E-Journal of Chemistry)
Cetyldimethylethylammonium bromide, a cationic surfactant has been used to decolorize eriochromeazurol B, an anionic triphenylmethane type of dye. Addition of specific lanthanide metal ion to this decolorized solution resulted into intense colored stable ternary complex with large bathochromic shift from 540 nm (binary complex) to 650 nm (ternary complex) with increase in absorbance values at shifted wavelength. CDMEAB thus decreases the color intensity of ECAB and increases the absorbance value of ternary complexes. This two fold advantage resulted into enhancement in molar absorptivities and sensitivities at shifted wavelength of ternary complexes with stoichiometric composition 1:(1:3)2, [Ln : (R:S)] for all lanthanides understudy namely yttrium, neodymium, europium, terbium and ytterbium. The ternary complexes at pH 6.0 exhibited absorption maxima at 650 nm with molar absorptivities 69000 L.mol-1.cm-2 for Y(III), 66000 L.mol-1.cm-2 for Nd(III), 69000 L.mol-1.cm-2 for Eu(III), 64000 L.mol-1.cm-2 for Tb(III), 70000 L.mol-1.cm-2 for Yb(III). Beer's law were obeyed in concentration range 0.11-0.94, 0.19-1.53, 0.2-1.41, 0.21-1.69 and 0.23-1.11 ppm for Y(III), Nd(III), Eu(III), Tb(III) and Yb(III) respectively. Conditional formation constants and various analytical parameters have been evaluated and compared the results of newly formed ternary complexes with binary complexes. Finally newly suggested modified method have been recommended for the microdetermination of lanthanides understudy.